Dermatoscopy in diagnosis of cutaneous myiasis arising in pemphigus vulgaris lesions - Keshavamurthy Vinay; Sanjeev Handa; Sumeeta Khurana; Sonu Agrawal; Dipankar De (Wolters Kluwer Medknow Publications, 2017)
Myiasis, infestation of live human and vertebrate animals by larvae, can complicate ulcers and open wounds. Although myiasis occurs in neglected erosions of pemphigus, such a complication is not documented in the literature. Herein, we report a case of myiasis complicating pemphigus vulgaris and describe its dermatoscopic features.